Delusions and the Predictive Mind. - Bongiorno, Federico; Corlett, Philip R (Australasian Journal of Philosophy, 2024)
A growing number of studies in both the scientific and the philosophical literature have drawn on a Bayesian predictive processing framework to account for the formation of delusions. The key here is that delusions form because of disrupted prediction error signalling. Parrott's recent critique argues that the framework is incomplete in two respects: (i) it leaves unclear why delusional hypotheses are selected over none at all, or over more plausible alternatives; and (ii) it leaves unclear how exactly it is that delusional hypotheses are generated in the first place. In this paper, we defend the framework's explanatory power by way of showing how it can go a long way in helping disentangle these concerns. We take up each of them in turn. As for the first, our argument turns on two claims: (a) believing nothing, although possible in principle, may not be a viable procedure in the circumstances; and (b) alternative hypotheses may be rendered unavailable for selection, due to aberrant prediction errors. As for the second concern, we distinguish three ways in which delusional hypotheses may be initially acquired, all of which are based on experience broadly construed.